KONSTRUKSI PRAKTIK AKUNTANSI TOLOBALANGO: STUDI ETNOMETODOLOGI ISLAM - Mohamad Anwar Thalib; Widy Pratiwi Monantun (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2022)
The aim of the study is to construct accounting practices at the Gorontalo engagement ceremony. This research uses an Islamic paradigm with an Islamic ethnomethodology approach. There are five stages of data analysis; amal, ilmu, iman, informasi wahyu, and ihsan (amiiin). The results of the study find that there are two ways that the Gorontalo community practiced accounting at the tolobalango ceremony; avoid non-material losses and finance the implementation of tolobalango. Both practices are driven by the spirit of mutual help (huyula) and kinship (o'ngalaa).